PENGARUH GOOD CORPORATE GOVERNANCE DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Sriatun, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2016)
Purpose of this research to knows: 1) effect of good corporate governance on ROA, 2) effect DER on ROA, 3) effect good corporate governance on value of manufacturing 4) effect DER on value of manufacturing, 5) effect ROA on value of manufacturing, 6) effect good corporate governance on value of manufacturing with ROA as intervening variables and 7) effect DER on value of manufacturing with ROA as intervening variables. This research are empirical study on conventional bank at Indonesia Stock Exchange. Population are conventional bank are listed Indonesia Stock Exchange. Sample used 30 bank with purposive sampling technique. Source data used secondary data. Collecting data used documentation and literature study. Data was analyzed used path analysis. Result showed that good corporate governance has positif but not significance effect on ROA. DER has negative and significant effect on ROA. Good corporate governance has positive but not significance effect on value of manufacturing. DER has positive but not signifance effect on value of manufacturing. ROA has positive and significance effect on value of manufacturing. Good corporate governance has positive and significant effect on value of manufacturingwith ROA as intervening variable. DER has positive and significance effect on value of manufacturing with ROA as intervening variables.Keywords: good corporate governance, DER, financial performance, value of manufacturing